Tympanoplasty in children: A review of 91 cases - Ribeiro, JC (2011)
OBJECTIVES: There is a marked diversity in the reported success rates for achieving an intact tympanic membrane following tympanoplasty. Controversy exists about the factors thought to influence surgical outcome. These facts have important implications for the selection of patients who would benefit the most. This study reviews the factors thought to determine the anatomical and functional success of tympanoplasty in children. MATERIALS AND METHODS: Retrospective study of the anatomical and functional results of 91 tympanoplasties performed in children. Age, gender, size and site of perforation, status of operated and contralateral ear, underlying cause of the perforations, surgical technique, pre-operative and post-operative hearing levels, post-operative follow-up time and post-operative complications were recorded. We divided our population into two groups according to the expected eustachian tube maturity (younger group (N=24): ≤10 years old, older group (N=67): >10 years old). All patients were evaluated in terms of anatomical and functional outcome and complications. RESULTS: Anatomical success was achieved in 85.7% and functional success was 76.9% after a mean follow-up of 25.6 ± 17.1 months. Anatomical success (intact tympanic membrane) was achieved in 83% of younger vs 87% of older patients (p=n.s.). Functional (air bone gap closure) success was 75% in the younger group vs 78% in the older group (p=n.s.). There were no significant differences in post-operative gain at different frequencies (500, 1000, 2000 and 3000 Hz) between the two groups. A previous adenoidectomy in children older than 10 years seems to be an independent predictor of functional success The incidence of minor and major complications were 29% in patients aged ≤10 and 21% in those older than 10 (p=n.s.). We report 12.9% minor post-operative complications in successful cases: injury to the chorda tympani nerve (5.7%), wound infection (2.9%), otitis externa (2.9%) and transient vertigo (1.4%). Among the 21 reperforations observed, 92.3% occurred before 1 year. CONCLUSIONS: This study shows that tympanoplasty is a valid treatment modality for tympanic membrane perforation in the pediatric population. A tympanic membrane perforation can be closed at any age. There is no age limit below which perforation should not be closed. A previous adenoidectomy in children older than 10 years seems to be an independent predictor of functional success.